THE EVOLUTION OF POLITICAL SYSTEM AND POLITICAL MODERNIZATION IN CHINA: PROBLEMS AND ADVANTAGES OF THE CHINESE MODEL - A. D. Voskressenski (Сравнительная политика, 2015)
I the context of socio-cultural specificity of the region, China presents a special case of gradual political modernization. Political stability is guaranteed as a result of the evolution of all spheres of political life while maintaining the basic political mechanisms. The article studies the mechanism of Chinese elite recruitment and rotation and the evolution of local-level electoral mechanisms, oriented at competitiveness raising at election time. The article concludes that gradual economic and political transformations during reform years led to the development of a specific Chinese civil society whose demands at the new phase of social development can only be met by further modernization of the political and economic systems.